2005
DOI: 10.1007/s00198-005-1988-z
|View full text |Cite
|
Sign up to set email alerts
|

Femoral neck geometry and hip fracture risk: the Geelong osteoporosis study

Abstract: To determine the relationship between femoral neck geometry and the risk of hip fracture in post-menopausal Caucasian women, we conducted a retrospective study comparing the femoral neck dimensions of 62 hip fracture cases to those of 608 randomly selected controls. Measurements were made from dual-energy X-ray absorptiometry scans (Lunar DPX-L), using the manufacturer's ruler function, and included: hip axis length (HAL), femoral neck axis length (FNAL), femoral neck width (FNW), femoral shaft width (FSW), me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
63
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(71 citation statements)
references
References 20 publications
5
63
3
Order By: Relevance
“…Proximal femoral strength is decreased with a varus mechanical axis 10,11 . Biomechanical studies have shown that trochanteric and femoral shaft fractures are more common in patients with low neck-shaft angles 12,13 . Koh et al reviewed the radiographs of forty-eight patients with atypical fractures and found that the fractures clustered in the lateral cortex at the region of maximal tensile loading 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Proximal femoral strength is decreased with a varus mechanical axis 10,11 . Biomechanical studies have shown that trochanteric and femoral shaft fractures are more common in patients with low neck-shaft angles 12,13 . Koh et al reviewed the radiographs of forty-eight patients with atypical fractures and found that the fractures clustered in the lateral cortex at the region of maximal tensile loading 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies suggest that HSA provides significant additional information to BMD in predicting the occurrence of hip fracture [35][36][37], especially at the femoral neck [38], not all studies agree [39,34,40]. The latter studies suggest that HSA indices provide prediction of fracture risk, but might not contribute additional information beyond BMD.…”
Section: Discussionmentioning
confidence: 99%
“…El-Kaissi et al [5] aimed to find out the relationship between femoral geometry and the risk of hip fracture in postmenopausal Caucasian women. Fractured patients had greater FSW and FAL than in controls.…”
Section: Nayak Et Almentioning
confidence: 99%